2021
DOI: 10.2147/opth.s301196
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Morphology of Peripapillary Retinoschisis

Abstract: Purpose We conducted cross-sectional examinations to determine the frequency of peripapillary retinoschisis (PRS) in eyes with glaucoma and suspected glaucoma and analyzed the pathogenesis of PRS by using spectral-domain optical coherence tomography (SD-OCT). Patients and Methods In 1516 cases involving glaucoma and suspected glaucoma, we retrospectively reviewed the disc and macular volume scans obtained by SD-OCT and categorized PRS into two groups based on whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Few studies have examined peripapillary retinoschisis in HM eyes; thus, our research provided additional evidence in this field. 29 31 Decreased macular and peripapillary ChT and increased PPA area have been reported in HM eyes. 32 34 In the present study, we found that macular ChT was associated with further thinning, and the PPA area was additionally enlarged after the occurrence of peripapillary retinoschisis.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have examined peripapillary retinoschisis in HM eyes; thus, our research provided additional evidence in this field. 29 31 Decreased macular and peripapillary ChT and increased PPA area have been reported in HM eyes. 32 34 In the present study, we found that macular ChT was associated with further thinning, and the PPA area was additionally enlarged after the occurrence of peripapillary retinoschisis.…”
Section: Discussionmentioning
confidence: 98%
“…In primary glaucoma dysfunction of photoreceptors, bipolar cells and horizontal cells are observed, as are changes in color and contrast sensitivity [85,87,91]. Peripapillary retinoschisis is observed in 1-6% of patients with all types of glaucoma [92][93][94][95][96] and associated with vitreous traction and dysfunction of Muller cells, and it correlates with disease progression. We suggest that discharge of the interstitial fluid into the vitreous is more likely as an explanation of peripapillary retinoschisis rather than vitreous traction because the PVD correlates with thickening of peripapillary fiber layer [97].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that two opposing forces provided by posterior staphyloma and anterior vitreous traction contribute to the formation of macular schisis ( 75 ). In addition, paravascular microfolds, cysts, and lamellar holes have been implicated in this mechanism ( 67 ).…”
Section: Papillary/peripapillary Schisismentioning
confidence: 99%